Thrust rebalance to extend engine time on-wing with consideration of engine degradation and creep life consumption - da Mota Chiavegatto, Rafael; Li, Yiguang (American Society of Mechanical Engineers (ASME), 2024)
Over the years, airlines have consistently attempted to lower their operational costs and improve aircraft availability by applying various technologies. Engine maintenance expenses are one of the most substantial costs for aircraft operations, accounting for around 30% of overall aircraft operational costs. So, maximizing aircraft time between overhaul is crucial to lowering the costs. The engine time on-wing is often limited due to the expiration of Life Limiting Parts, performance deterioration, etc. This paper presents a novel method of rebalancing the thrust of engines of an aircraft to maximize the time between overhaul of the aircraft considering the performance degradation and creep life consumption of the engines. The method is applied to a model aircraft fitted with two model engines similar to GE90 115B to test the feasibility of the method with one engine degraded and the other engine undegraded. The obtained results demonstrate that for the aircraft flying between London and Toronto with 5,000 nominal flight cycles given to the engines, the time on-wing of the degraded engine could drop from 5,000 to 2,460 flight days due to its HP turbine degradation (1% efficiency degradation 3% flow capacity degradation), causing the same level of drop of time between overhaul of the aircraft. The time on-wing of the degraded engine could increase from 2,460 flight days without thrust rebalance to 3,410 flight days with thrust rebalance, i. e. around 38.6% potential improvement for the time between overhaul of the aircraft at the expenses of increased creep life consumption rate of the clean engine. The proposed method could be applied to other aircraft and engines.
Keywords: Gas Turbine; Engine; Thrust Rebalance; Creep Life; Performance Degradation